Direct and indirect effects of central stoneroller (Campostoma anomalum) on mesocosm recovery following a flood: can macroconsumers affect denitrification? - Reisinger, Alexander J.; Presuma, Dumi L.; Gido, Keith B.; Dodds, Walter K. (My University, 2011)
Anthropogenic N loadings and perturbations of macroconsumer communities impair ecological and economic services provided by streams. Organisms are adapted to natural disturbances, such as flooding and desiccation, but how anthropogenic and natural disturbances interact is poorly understood. We used large outdoor mesocosms to study the effect of Campostoma anomalum, a common prairie headwater-stream minnow, and NH4 + additions (to simulate fish excretion) on the recovery of ecosystem structure and function following a flood, highlighting the potential for Campostoma (and other macroconsumers) to affect denitrification. Campostoma and NH4 + treatments differentially affected particulate organic matter size and filamentous algal structure. Ecosystem structure responded differently to mesocosm treatment over time, a result suggesting that grazers or NH4 +-N availability may be especially important during early recovery periods. The presence of Campostoma did not influence denitrification, but NH4 + additions altered the response of denitrifiers to nutrient and energy amendments, and denitrification rates decreased following the recovery of mesocosms. Temporal changes in denitrification probably were caused by increasing hyporheic dissolved O2 concentrations, which led to potentially fewer anoxic microsites for production of denitrification enzymes. Our study shows that grazers affect the recovery of ecosystem structure, but denitrification in the context of these prairie-stream mesocosms appears to be unaffected by Campostoma.
Keywords: Campostoma; Grazer; Prairie streams; Flood recovery; Denitrification; Ecosystem function; Mesocosm